The experiences of people living with HIV/AIDS in Gaborone, Botswana - Setlhare, Vincent (My University, 2008)
ABSTRACT Study Aim and Objectives: The aim of the study was to explore what it means to have HIV/AIDS in Gaborone, Botswana. The study describes the demographic and socioeconomic circumstances of the participants. It also elicits and explores the experiences of people living with HIV/AIDS in Gaborone, Botswana. Methods Interviewees were purposely selected from a hospice, an NGO and a church that ministers to PLWHA. In depth interviews were conducted and recorded by audiotape. The interviews were conducted in Setswana and the interviewees responded to a statement, which essentially was, “Tell me about your life since you knew you had HIV/AIDS”. The audio recordings were transcribed into English. Care was taken to carry the Setswana way of speaking directly into English. A thematic analysis of the transcripts was made. A modified cut and paste method was used to gather the information into its various themes. Results There were 15 interviewees. Their average age was 35.3 years and on average, they had 1.6 children each. They were unemployed. The interviewees described a wide range of experiences, which were not necessarily experienced by all. Their narratives described the physical symptoms they suffered. They described stigma and discrimination that they went through. They gave accounts of psychological and emotional turmoil. Psychiatric problems were cited. They were very concerned that they could no longer support their children. They also worried about what would happen to their children when they died. As their disease progressed, they lost their jobs and were reduced to poverty. They could no longer support themselves and their dependents. They depended on relatives, friends, NGOs and government for relief. Relief from friends and relatives was often not available. They suffered hunger, as they could not satisfy their increased appetites after they started ARV drug therapy. Their relationships were disrupted when they got ill. Spouses and friends left and some relatives and friends stigmatised them. Interviewees were taken care of by relatives, friends, health professionals, NGOs, and social workers. In all these categories, there were good and bad care givers except the hospice and church, which were reported as good caregivers. Caregiver fatigue was described. Some interviewees found comfort in God. They believed that He knows what they are going through and will take care of them. The interviewees also found comfort and healing from the companionship of other PLWHA. The interviewees wanted to find jobs and work so that they could support themselves and their dependents. They wished government would train them and find them jobs. Conclusion The study confirmed the psycho-emotional problems and concern for children felt by PLWHA, that the literature revealed. It showed the physical problems they also suffer. The study revealed that interviewees lost jobs and became destitute. They could not satisfy their increased appetites after they started ARV drug therapy. Interviewees’ relationships were disrupted when they got ill. Spouses and friends left and some relatives did not treat them well. There were good and bad care givers in different categories. The African custom of botho/ubuntu seems to be succumbing to the onslaught of HIV/AIDS. The study showed that interviewees found comfort and support from family, friends, NGO’s and the church. They found God and other PLWHA especially valuable support systems. It was encouraging to notice that some interviewees felt that with time, stigmatisation of PLWHA is gradually subsiding.
Keywords: living with HIV/AIDS; Gaborone, Botswana